Quantum effects in silicon for photovoltaic applications. Issue 6 (8th February 2013) - Ingenhoven, P.; Anopchenko, A.; Tengattini, A.; Gandolfi, D.; Sgrignuoli, F.; Pucker, G.; Jestin, Y.; Pavesi, L.; Balboni, R.
Abstract Quantum confinement effects in silicon might help to overcome the theoretical efficiency limit of ∼33% of silicon cells [Shockley and Queisser, J. Appl. Phys. 32, 510 (1961)]. The dominant loss mechanism in solar cells is the thermalization of photo‐excited carriers to the band gap. Engineering of the band gap makes it in principle possible to obtain a conversion efficiency of ∼44% [Pavesi and Turan (eds.), Silicon Nanocrystals, Fundamentals Synthesis and Application (Wiley‐VCH, Berlin, 2010)]. Band gap engineering is achieved by controlling the silicon‐nanocrystal (Si‐NC) dimension. We currently use Si‐NCs in solar cells to modify the solar spectrum in a way that the incoming light is more efficiently converted into electricity and also, to realize multiple junction cells to minimize thermalization losses. The Si‐NC energy of the band gap and the Si‐NC optical properties depend strongly on the NC size, which can be controlled by the processing parameters. Therefore, light management is possible by varying the refractive index of the Si‐NCs to improve the antireflective coating (ARC) and by conversion of absorbed high energy photons re‐emitted in the red spectral region of light. Thus, in this approach Si‐NCs are used as spectral down‐shifters and for ARC optimization. Further, NCs allow the fabrication of higher band gap solar cells, to be used on top of standard silicon cells as tandem cell elements. Due to the tunability of the band gap, it is possible to construct all silicon multilayer or tandem cells. The concepts and research results for both ideas will be presented.